2002
DOI: 10.1002/ps.534
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of responses to pheromone by (Z)‐11‐hexadecenyl trifluoromethyl ketone, an analogue of the pheromone, in the cabbage armyworm Mamestra brassicae

Abstract: The effects of (Z)-11-hexadecenyl trifluoromethyl ketone (Z11-16:TFMK) a fluorinated pheromone analogue, on the responses to sex pheromone of the male cabbage armyworm, Mamestra brassicae, have been investigated in an actograph and by electroantennography (EAG). In spite of its structural proximity with the natural pheromone, Z11-16:TFMK was poorly active in EAG, and not active on male behaviour. When permeated in the air, Z11-16:TFMK reversibly inhibited the electroantennographic responses to (Z)-11-hexadecen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 22 publications
(34 reference statements)
0
5
0
Order By: Relevance
“…Synthetic compounds can also alter the peripheral responses of insects. For example, trifluoromethyl ketone mimics of pheromones interfere with the EAG responses , , , and with the behavior of the insects toward their pheromone , , . Another example is DEET: it caused either a decrease or an enhancement in the response to food odors of selected olfactory neurons in Drosophila .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Synthetic compounds can also alter the peripheral responses of insects. For example, trifluoromethyl ketone mimics of pheromones interfere with the EAG responses , , , and with the behavior of the insects toward their pheromone , , . Another example is DEET: it caused either a decrease or an enhancement in the response to food odors of selected olfactory neurons in Drosophila .…”
Section: Discussionmentioning
confidence: 99%
“…In nature, host plant odors have been known to synergize with pheromone responses and nonhost plant odors sometimes antagonize pheromone responses . Natural or synthetic pheromone mimics can also antagonize the response of an insect to its pheromone , .…”
Section: Introductionmentioning
confidence: 99%
“…In brief, the inhibitory activity of TFMKs is due to a stable hemiacetal of tetrahedral geometry that is formed between the conserve serine residues of the antennal esterases with the highly electrophilic carbonyl (Durán et al, 1993;Wiedemann et al, 1998). Some studies have been performed with TFMKs and electrophysiological assays in Plutella xylostella (Prestwich and Streinz, 1988), Thaumetopoea pityocampa (Parrilla and Guerrero, 1994), M. brassicae (Renou et al, 2002), Cydia pomonella (Giner et al, 2009), and S. frugiperda (Malo et al, 2013). Moreover, TFMKs have been used with antennal extracts of different moth species, e.g., S. littoralis (Durán et al, 1993), Ostrinia nubilalis (Riba et al, 2005), and C. pomonella (Giner et al, 2009).…”
Section: Antennal Esterases Inhibition In Integrated Pest Managementmentioning
confidence: 99%
“…The strict structural analogies to the natural pheromone could make the fluoro analogue 178 a good substrate for receptor recognition and transduction processes. The same compound was submitted107 to actographic investigation performed on Mamestra brassicae males. The actographic analysis showed that the latency of the response was proportional to the doses of the trifluoromethyl ketone and that the percentage of responding males was not affected.…”
Section: The Pheromonal Communication System Of Insectsmentioning
confidence: 99%